2003
DOI: 10.1111/j.0303-6979.2004.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Enamel matrix proteins in the treatment of intra‐bony defects

Abstract: The surgical procedure used in the present study, aiming for maximum preservation of the regenerative potential of periodontal tissues, showed per se excellent results. The use of EMD as an adjunct to periodontal surgery in the treatment of angular defects possibly enhances periodontal regeneration rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0
22

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(105 citation statements)
references
References 21 publications
4
79
0
22
Order By: Relevance
“…Bone levels after the use of EMDP may be compared with the initial bone levels as an interesting outcome. Eleven studies (10,15,16,(23)(24)(25)27,29,36,39,41) observed bone filling in radiographs, and in only one study it was performed in re-entry surgeries (14). Nevertheless, it is important to point out that bone measurements do not reflect connective attachment levels.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Bone levels after the use of EMDP may be compared with the initial bone levels as an interesting outcome. Eleven studies (10,15,16,(23)(24)(25)27,29,36,39,41) observed bone filling in radiographs, and in only one study it was performed in re-entry surgeries (14). Nevertheless, it is important to point out that bone measurements do not reflect connective attachment levels.…”
Section: Discussionmentioning
confidence: 99%
“…It could be hypothesized that this heterogeneity may be explained by the fact that some studies used antibiotics (14)(15)(16)24,25,27,29,34) and others did not (10,17,23,26,28,30,35), by the variable surface treatments, inclusion of smokers (10,(14)(15)(16)(17)(23)(24)(25)28,29,34,35), initial depth of defects and number of remaining bone walls, use of placebo gel in some studies (10,15,16,27,34) and not in others (14,17,23-26,28,29,35), differences in methodological quality, in addition to other variables that could influence the results, such as the surgical technique, quality of instrumentation and biofilm control performed by the patients (45).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations